Critical Discourse Analysis An Introduction to Major Approaches - Moslem Ahmadvand (Universitas Stikubank (UNISBANK) Semarang, 2011)
Meaning is not a monolithic construct; it is a multidimensional and slippery concept with amazing complexity. Understanding the silent meaning of a text, be it spoken or written is a highly-needed skill in the modern era, for the exposure to information and media is so vast that one can never be sure of the validity of the surrounding information. Critical Discourse Analysis along with other related disciplines attempts to reveal hidden meanings, that is, the ideological loads of the discourse. This paper tries to review the origins of CDA and introduces some of the influential theoretical schools on it. Although these approaches differ in terms of the theoretical foundations and analytic tools, they share three concepts of critique, power, and ideology. This article emphasizes two major points. One is the dialectic relation between society, culture, politics, and language that this complex relation requires multidisciplinary research. The other is the fact that CDA cannot be taken as theory due to its tendency to adopt an eclectic approach in the analysis of the data. Key words: critical discourse analysis, critical linguistics, ideology, text, power.